Pengaruh Konseling Individual Menggunakan Psikoterapi Islam Terhadap Depresi Pada Remaja - Desty Malika; Isak Iskandar (Jurnal Riset Multidisiplin Edukasi, 2025)
Depression in adolescents is a serious problem that affects psychological, social, and spiritual aspects. Adolescence is marked by significant changes that are prone to causing stress, so a comprehensive healing approach is needed. This study aims to analyze the effect of individual counseling based on Islamic psychotherapy in treating depression in adolescents. Islamic psychotherapy is used as a method that not only touches the psychological aspect but also strengthens the spiritual dimension of adolescents through the values ​​of monotheism, patience, gratitude, and dhikr. Individual counseling is an effective medium for building an empathetic and accepting therapeutic relationship. The results of the analysis show that this therapy is able to reduce symptoms of depression, increase peace of mind, and improve adolescent social relations. Islamic psychotherapy is not only curative, but also preventive, providing strong mental strength through a deep spiritual approach. Thus, the integration of psychological counseling and Islamic values ​​is a relevant and effective approach in efforts to restore the mental health of Muslim adolescents in the modern era.